QUESTION FORMATION OF BAHASA INDONESIA AS A SECOND LANGUAGE - Sakhiyya, zulfa (Universitas Pendidikan Indonesia, 2013)
Abstract: This article aims to implement Processability Theory (PT) to Bahasa Indonesia or Indonesian language and to identify developmental stages for question formation in the setting of Bahasa Indonesia as a second language (ISL). PT provides a theoretical framework in making predictions about the course of language development, in this case the question formation acquisition. This study proposes developmental stages of question formation in ISL setting by contrasting the lexical functional grammar of Indonesian question as compared to ESL question formation. Four stages of ISL question formation were proposed. The proposed stages serve as the basis for data analysis and to show its plausibility.